2001
DOI: 10.2116/analsci.17.1355
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Anthraquinone Dye, C.I. Disperse Violet 27

Abstract: The title compound, 1-anilino-4-hydroxyanthraquinone (Fig. 1), has been developed and used as an anthraquinone dyestuff called C.I. (Color Index) Disperse Violet 27 (C.I. 60724). 1,2 Despite the commercial significance of this dye class, a search of the literature suggested that the crystal structures of the anthraquinone dyes had not been published. With these points in mind, this paper presents the results of an X-ray analysis of the title compound during the course of our investigation concerning the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Accordingly, the technical performance and functionality of the disperse dyes have strong relationship with their particle size, morphology as well as crystal structure arrangement [15]. As part of longterm program for the investigation of structure/function relationships for the dye molecules, our group has reported the crystal structures of some disperse dyes such as monoazo [11], methine [12] and anthraquinone [13] dyes. Recently we were successful to prepare the single crystals of C.I.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the technical performance and functionality of the disperse dyes have strong relationship with their particle size, morphology as well as crystal structure arrangement [15]. As part of longterm program for the investigation of structure/function relationships for the dye molecules, our group has reported the crystal structures of some disperse dyes such as monoazo [11], methine [12] and anthraquinone [13] dyes. Recently we were successful to prepare the single crystals of C.I.…”
Section: Introductionmentioning
confidence: 99%
“…860 (4) 7683 (2) 1039 (2) 22(1) C(4) À121(4) 8571 (3) 1279 (2) 27(1) C (5) 108 (4) 9262 (3) 2169 (2) 26(1) C (6) 1355 (4) 9076 (2) 2849 (2) 23(1) C (7) 2335 (4) 8209 (3) 2617 (2) 24(1) C (8) 2097 (4) 7494 (3) 1719 (2) 25(1) C (9) 1047 (4) 11228 (3) 4878 (2) 24(1) C(10) 5(4) 12091 (3) 5061 (2) 26(1) C (11) 185 (4) 12863 (3) 5925 (2) 26(1) C (12) 1439 (4) 12738 (3) 6630 (2) 29(1) C (13) 2492 (4) 11898 (3) 6470 (2) 31(1) C (14) 2327 (4) the acetonitrile solution of the purified dye after two weeks of storage in a refrigerator. The crystal used exists in the triclinic space group P-1.…”
Section: Resultsunclassified
“…As part of a research study concerning the structure/function relationships of dye molecules, we have reported the crystal structures of several types of disperse dyes such as monoazo [12,13], methine [14] and anthraquinone [15] classes. As a continuation of this research, we describe herein the crystal structure of C.I.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the demand for the development of new functional dyes also requires additional information including the structural conformations of already existing dyestuff in molecular level. As a part of research program for the structure/function relationships of the dye molecules, we have reported the crystal structures of several types of disperse dyes such as monoazo [12][13][14], methine [15] and anthraquinone [16] dyes. In particular, disperse azo dyes have been continuously used in the paper, foodstuffs and leather as well as textile industry [1].…”
Section: Introductionmentioning
confidence: 99%